Artribut-atribut Celebrity Endorser JKT48 yang Mempengaruhi Niat Beli Erigo - Supriyatno, Christianus Adityo; Simamora, Bilson (Global Research on Economy, Business, Communication, and Information, 2023)
A celebrity endorser is an individual known by the wider community and uses this recognition to appear with the name of the consumption of goods in one advertisement. Erigo products are endorsed through celebrity endorser JKT48. It is not yet known whether JKT48 affects the success of the Erigo product. Therefore, the problem of this research is whether using the JKT48 celebrity endorser can influence the purchase intention of Erigo products. This study uses reference group theory as a fundamental theory, which states that reference groups increase consumer confidence and knowledge about products to influence purchase intentions. Respondents in this study were Erigo and JKT48 Instagram followers. The retrieval technique was done by distributing questionnaires online using a Google form with a sample of 155 respondents. The data analysis technique is Structural Equation Modeling (SEM). Data is processed using WarpPLS 7.0 and SPSS 26. The study shows that visibility has no significant effect on purchase intention, credibility has a positive and significant influence on purchase intention, attractiveness has no significant effect on purchase intention, and power has a positive and significant influence on purchase intention. The study inspires that companies must choose the right endorser. Selection of the right endorser can influence purchase intentions because it can increase purchase intentions for the products offered.